Effects of the unilateral lesion of the substantia nigra compacta with 6-OHDA on reversal learning and prepulse inhibition in male and female Wistar rats (2023)
Background: Motor impairments in Parkinson's disease (PD) are associated with alterations in the prepulse inhibition (PPI) of the acoustic startle response (ASR) and reversal learning (RL) from the early stages of the disease. In this context, animal models enable the exploration of the dynamics of non-motor manifestations associated to dopaminergic depletion in a time-dependent manner. Method: 103 adult male and female Wistar rats received unilateral injections of 6-OHDA or saline into the Substantia Nigra Compacta (SNc). Motor skills and the PPI were assessed before and after surgery. Subsequently, three groups were formed to evaluate action-based RL (AB) and stimulus-based RL (SB). Results: The apomorphine test at 2 weeks confirmed the establishment of dopaminergic depletion. Motor coordination was affected in the lesioned groups, with higher number of grip errors and reduced running speed in lesioned males 6 weeks after surgery. The percentage PPI decreased in lesioned females at 4 weeks but increased in lesioned males 6 weeks after lesioning. Finally, the 6-OHDA lesion did not affect initial discrimination or reversal in the AB task, although a treatment facilitation effect was observed in the reversal of SB task. Additionally, sex-dependent differences were observed in performance. Males showed more perseverative behavior and a higher percentage of the win-stay strategy, while females exhibited slower response latencies for both correct and incorrect responses, displaying a higher percentage of the lose-shift strategy. Conclusion: The results show that subthreshold dopamine depletions in the SNc in the unilateral rodent model of 6-OHDA caused sex-differential effects on PPI and RL with more noticeable motor impairments in males after six weeks after surgery. Further characterization of how PPI and RL changes over time in the absence of motor impairments in early stages of dopamine depletion may contribute to anticipate PD diagnosis in human patients and to develop early tailored and more effective sex-dependent treatments.